اقوال شبستری در گلشنِ راز و تاویلِ قرآنی: بین السطورِ تصوف و کلام کا استدلالی مطالعہ: The Sayings of Shabistarī in Gulshan-i Rāz and Qurʾānic Hermeneutics: An Analytical Study between the Lines of Sufism and Kalām (Al-Qamar, 2025)
This study offers an analytical and interpretive exploration of Maḥmūd Shabistarī’s Gulshan-i Rāz within the dialectical framework of Islamic mysticism (taṣawwuf) and scholastic theology (ʿilm al-kalām). It seeks to uncover the epistemological foundations of Shabistarī’s thought and his method of Qurʾānic taʾwīl (esoteric interpretation), situating his mystical insights in conversation with rational theological discourse. By examining key poetic aphorisms and symbolic expressions in Gulshan-i Rāz, the research investigates how Shabistarī harmonizes reason and revelation, and how his metaphysical interpretations of Qurʾānic verses reflect both intuitive unveiling (kashf) and intellectual reasoning (ʿaql). Through a critical comparison with classical theologians such as al-Ghazālī, Fakhr al-Dīn al-Rāzī, and Ibn ʿArabī, the paper elucidates how Shabistarī’s hermeneutical approach transcends literalism without departing from the essence of tawḥīd. The study concludes that Gulshan-i Rāz represents a unique synthesis between Sufi symbolism and kalāmic rationality, demonstrating that mystical exegesis in Islam operates as a dynamic dialogue between text, intellect, and spiritual experience.
Keywords: Shabistarī, Gulshan-i Rāz, Qurʾānic hermeneutics, taʾwīl, Sufism, kalām, tawḥīd, kashf, rational theology, Islamic mysticism